'The Fire Does Not Disturb Us': Navigating Love, Desire and Loss in the Qaṣīda Poetry of South Sinai Muzīna Women. Issue 2 (1st December 2021) - Sparks, Matthew Ryan
Abstract: This article examines the contemporary qaṣīda poetry of South Sinai Muzīna Bedouin women from an anthropological perspective, drawing primarily upon a history of emotions framework, as well as Bedouin ethnographic studies and Arabic literary criticism. The article argues that the composition and vocalisation of qaṣīda poetry in South Sinai is more than a performative art; it is a means of 'navigating' one's emotions as a woman in a patriarchal society where emotional expression for both men and women is deemed inappropriate. In the poetry of Nādiyyah and Umm 'Īd, we gain insight into the subjective lived experience of Bedouin women in South Sinai, as they attempt to poetically express their desire, elation, grief and passion, while simultaneously demonstrating their ability to 'control' their emotional states.